Adolescents added to social networks and techn (Horizontes de Enfermería, 2018)
The research was carried out in adolescents from Tulcán Educational Unit, with the objective of identifying the addiction to social networks and technology and the psychological alterations that are generated. Nowadays technology has been one of the best advances for science, being an indispensable tool to generate new knowledge, but it has undoubtedly also contributed to many adolescents using it in an inadequate way generating different problems in their psychological and social health. A descriptive, qualitative and quantitative study was carried out using the research technique and the application of a test. When the research was carried out it was possible to show that 53% have nomophobia, 37% dedicate 3 to 5 hours a day to social networks, 55% affirm that they are in a bad mood because they are not connected and can not exchange information with their virtual friends, 59% say they are affected in their sleep hours due to addiction to social networks, 78% prefer virtual life than the real world. It was concluded that excessive use of social networks, can cause addiction like any other substance or typical behavior. These contribute to the dispersion of social cohesion, since their use has been misrepresented, mainly by adolescents. The strong addictive capacity of the Internet is greatly increased by its wide availability, low cost and easy handling.
Keywords: Addiction; social networks; teenagers